A Review of Sharia Economic Law on Tax Reform in Indonesia - Lisa Aula Hasibuan; Jundi Zakiyah; Ariq Athaullah; Frans Rahma Amanda Lubis; Abdul Rahman Malik Siregar (ISNU Nine-Star Multidisciplinary Journal, 2025)
Tax reform is a crucial component of reforming the tax system to improve fairness, efficiency, and state revenue. From the perspective of Islamic economic law, tax reform must prioritize the principles of distributive justice, public welfare, and balance. This article aims to examine tax reform from an Islamic legal perspective, particularly regarding the extent to which the policy aligns with Islamic values. This research uses a normative approach with a literature review method. The results indicate that tax reform is acceptable under Islamic law if it meets the principles of the maqasid of Islamic law and does not unjustly burden the people. The integration of zakat (alms) into the tax system is also an important agenda for achieving fiscal justice that balances taxes and religious obligations.